Tenofovir as Rescue Therapy Following Clinical Failure to Lamivudine in Severe Acute Hepatitis B - Jurgen Gerada; Elaine Borg; Denise Formosa; Rosalie Magro; James Pocock (Mediterranean Journal of Hematology and Infectious Diseases, 2013)
Acute hepatitis B (AHB) is a self-limiting condition in more than 95% of cases. Treatment is however recommended in patients with severe AHB (<1% of cases), aiming to prevent liver failure and death. Various nucleos(t)ide analogues (NA) have been found to be effective in severe AHB, although NA-resistant strains causing AHB have been also recently reported. The use of tenofovir in this setting has only been reported once with a favorable outcome. We hereby report a 47-year-old treatment-naïve male, who developed severe AHB and was treated with lamivudine (LMV). Initial rapid biochemical response was followed by biochemical breakthrough after 9 days, suggesting LMV resistance. Rescue therapy with ‘add-on’ tenofovir brought about a sustained improvement in biochemical, serological and virological markers until HBsAg was lost after 4 months. Thus, this is the second case reporting the successful use of tenofovir in severe AHB.